Exploring views and experiences of the general public's adoption of digital technologies for healthy lifestyle in Singapore: a qualitative study - Kumarasan Roystonn; P. V. AshaRani; Fiona Devi; Peizhi Wang; Yunjue Zhang; Anitha Jeyagurunathan; Edimansyah Abdin; Lorainne Tudor Car; Lorainne Tudor Car; Siow Ann Chong; Mythily Subramaniam; Mythily Subramaniam (Frontiers Media S.A., 2023)
ObjectiveLittle is known about the general adult population's adoption of digital technology to support healthy lifestyle, especially when they are expected to take greater personal responsibility for managing their health and well-being today. The current qualitative study intended to gain an in-depth understanding of determinants of digital technology adoption for healthy lifestyle among community-dwelling adults in Singapore.DesignA qualitative study design, with thematic framework analysis was applied to develop themes from the data.SettingSemi-structured individual interviews were conducted with participants either face-to-face or online through a videoconferencing platform.Participants14 women and 16 men from the general population who were between the ages of 22 and 71 years.ResultsThree major themes were developed: (1) digitally disempowered (2) safety and perceived risks and harm; (3) cultural values and drives. Adoption of technology among the general population is needs-driven, and contingent on individual, technological and other cross-cultural contextual factors.ConclusionOur findings highlight there is no one solution which fits all individuals, emphasizing the challenges of catering to diverse groups to reduce barriers to adoption of digital technologies for healthy lifestyle. Digital guidance and training, as well as social influences, can motivate technological adoption in the population. However, technical problems as well as data security and privacy concerns should first be adequately addressed. This study provides rich cross-cultural insights and informs policy-making due to its alignment with government public health initiatives to promote healthy lifestyle.